Attitude Control of Quadrotor - Nurul Amirah, Ismail; Zainah, Md. Zain; Pebrianti, Dwi; Bayuaji, Luhur (2015)
This paper presents the attitude behaviour of quad-rotor by using a LQR controller. The performance of the LQR controller is compared to a PD controller. The controller is designed by using mathematical approaches and the results are obtained through the MATLAB simulations in the term of settling time and overshoot percentage.